Effects of Noradrenaline on the Membrane Potential of Prostatic Neuroendocrine Cells of Rat - JunHeeKim; SunYoungShin; 엄대용; 김성준 (The Korean journal of physiology & pharmacology, 2003)
KCI Citation Count: 0